The history of privatization and re-privatization of PJSC Ukrtelecom - Mostovenko, O. O. (Ways to Improve Construction Efficiency, 2019)
The privatization of strategic assets, which was announced last year, has not yet begun. In 2018, the State Property Fund of Ukraine plans to bid 893 enterprises for privatization and receive UAH 22.5 billion from privatization. One of the reasons is that it is difficult for potential investors to understand the legal framework and the conditions in which the entire law enforcement system operates. The purpose of the study is to identify the main problems, obstacles, mechanisms of privatization of state-owned enterprises on the basis of the historical analysis of privatization and re-privatization of PJSC “Ukrtelecom”, which is a typical example of privatization of large strategic objects of the country. The article discusses the history of privatization of state-owned enterprises, in particular the advantages and disadvantages of the decision to re-privatize the strategic object of Ukrtelecom PJSC and the reasons for the return to the state ownership of a stake in the enterprise. A comparative analysis of the company development indicators, including the number of staff and the volume of local telecommunication services and Internet services from 2007 to 2018, was found. Privatization did not help to increase the efficiency of the company, but its indicators are steadily decreasing. Thus, in 2007, the company employed 105 thousand people, and in 2018 - 25 thousand people. The volume of services is also steadily declining. Also, the owner does not invest in the company, which was a condition for privatization. Failure by the new owner of social and other obligations, which may be grounds for re-privatization of the company. Despite numerous attempts to oblige investors to fulfill their commitments, the company continues to be in a state of contraction. But attempts at re-privatization have not been implemented at this time. The analysis showed that in times of fighting in the country, the investment climate is unstable and volatile, the issues of re-privatization should be approached with caution. Thus, the re-privatization of Ukrtelecom may adversely affect the investment flow in Ukraine, and this negative factor may affect the plans of the Cabinet of Ministers of Ukraine for large-scale sale of state assets, creating so-called "image losses" of the country.